PERAN TANAH WAKAF DALAM MENINGKATKAN KESEJAHTERAAN PEREKONOMIAN DI MASYARAKAT KECAMATAN PULAU TEMIAN TEBO ULU - Futri Yani; H. Sissah; Syahril Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This thesis is entitled The Role of Waqf Land in Improving the Economic of the Temiang Island Community in Tebo Ulu. This research uses qualitative research methods. The types and sources of data needed are primary data and secondary data. Data collection techniques are carried out by means of observation, interviews and documentation, while data analysis methods include data collection, data reduction, data presentation and drawing conclusions. The results of this research show the role of Waqf Land in improving the economic welfare of the people of Temiang Island in Tebo Ulu, namely that many people depend on the income they get from trading in the market and most people fulfill their needs. From a spiritual aspect, it provides very positive results and the role of waqf land which is managed as an elementary school building becomes a forum for the local community to teach children and provide insight. The obstacles faced by the management of the role waqf are the lack of competent human resources and the status of the role waqf land does not yet have a certificate and there is a lack of ways to educate the people on Temiang Tebo Ulu Island. The solution that can be implemented is to increase human resources by providing training and guidance to the community and the management of the Nurul Ihksan Mosque and increasing socialization to the community regarding waqf both online and in person